Edukasi Peran Vitamin dalam Menjaga Imunitas pada Siswa SMP Muhammadiyah 5 Samarinda - Fahdianto, Arifin Nur; Astutik, Anggun Puji; Amilia, Andini Nur; Helmi, Helmi (Universitas Pahlawan Tuanku Tambusai, 2026)
Adolescence is a crucial growth period requiring optimal micronutrient intake, yet many Indonesian adolescents lack sufficient vitamin consumption. This health promotion activity aimed to enhance the knowledge of students at SMP Muhammadiyah 5 Samarinda regarding the role of vitamins in maintaining immunity. The method involved interactive counseling using PowerPoint presentations and the distribution of educational leaflets to 28 students. Knowledge was measured using pre-test and post-test instruments. Results showed a significant increase in average knowledge scores, from 65% in the pre-test to 89.29% in the post-test. Two-way discussions and visual media proved effective in facilitating cognitive changes among participants. In conclusion, this education successfully strengthened students' health literacy regarding the importance of vitamins for the immune system. This community-based health promotion innovation is recommended for replication to support sustainable adolescent health.